2009
DOI: 10.4028/www.scientific.net/amr.79-82.147
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Feasibility of Bacterial Cellulose as Tissue Engineering Scaffold

Abstract: OBJECTIVE: As a kind of nanometer natural material, bacterial cellulose (BC) has been widely used in the field of food processing, paper making, pharmaceutical science, etc. In recent years, it is found that there is a good application potentiality of BC used in the medical science, especially in the field of regeneration medicine. There are some reports about BC being used in tissue engineering. It is of great necessity to investigate its tissue compatibility. In this research, the cell compatibility of BC wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In a comparison of the mechanical properties of the purified cellulose samples, hydrogels before drying (not dried) and dehydrated, significantly higher (49 ± 3.6%) deformability of the fresh hydrogels compared to 18.5 ± 08% for dehydrated samples was found, while Young's modulus in fresh samples was lower by at least two orders of magnitude (1.5 ± 0.3 vs. 250.4 ± 20.1 MPa). The found values for tensile strength and elastic modulus for wet fresh samples were comparable to those reported for the pig carotid artery (tensile strength 1.0 ± 0.2 MPa, Young's modulus 2.3 ± 0.1 MPa), which makes it possible in the future to consider it as a framework for tissue engineering [43].…”
Section: Mechanical Properties Of the Bc Samplessupporting
confidence: 81%
“…In a comparison of the mechanical properties of the purified cellulose samples, hydrogels before drying (not dried) and dehydrated, significantly higher (49 ± 3.6%) deformability of the fresh hydrogels compared to 18.5 ± 08% for dehydrated samples was found, while Young's modulus in fresh samples was lower by at least two orders of magnitude (1.5 ± 0.3 vs. 250.4 ± 20.1 MPa). The found values for tensile strength and elastic modulus for wet fresh samples were comparable to those reported for the pig carotid artery (tensile strength 1.0 ± 0.2 MPa, Young's modulus 2.3 ± 0.1 MPa), which makes it possible in the future to consider it as a framework for tissue engineering [43].…”
Section: Mechanical Properties Of the Bc Samplessupporting
confidence: 81%
“…Despite their abundance in nature, excellent mechanical properties and biocompatibility [63][64][65][66][67][68] , the use of cellulose in tissue engineering applications has been limited in part due to the lack of an environmentally benign processing method. Our approach for using ionic liquids both as common, environmentally benign solvents to dissolve pure cellulose and for blending with silk may help overcome any reluctance to use these natural materials as scaffolds for chondrogenic differentiation of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their prepared BC/SF:50% scaffold led to improved biocompatibility and suitability to induce cell adhesion, in comparison with pure BC scaffolds. 115 The BC-Si formulations exhibited a defined, interconnected porous network, the best outcome and stability being provided by a 50% SF content, which shows a major increase in cell adhesion and higher rates of cellular viability, as compared to pure BC. The genotoxicity test revealed that the material is non-genotoxic, indicating safety for medical applications, especially in tissue regeneration.…”
Section: Bone Tissue Engineeringmentioning
confidence: 93%
“…Barud et al prepared non-genotoxic BC-silk fibroin (SF) porous scaffolds to be applied successfully and safely in tissue regeneration. 115 It was found that the pore sizes of a scaffold matrix affect the mechanism and the rate of cell adhesion, migration and proliferation, and influence directional growth of the tissue into the matrix. Furthermore, their prepared BC/SF:50% scaffold led to improved biocompatibility and suitability to induce cell adhesion, in comparison with pure BC scaffolds.…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%